18 Strain Mapping In The Achilles Tendon. (5th September 2014) - Bogaerts, Stijn; Desmet, Hannelore; Peers, Koen
Abstract : Introduction: Achilles tendinopathies continue to present in epidemic-like proportions. Due to its multifactorial aetiology and its fragmentarily understood pathophysiology, the management of Achilles tendinopathy is time-consuming and therefore often frustrating. Nevertheless, eccentric exercises have emerged as the key element in the treatment of these tendinopathies. However, to date, there is no general agreement on the optimal eccentric exercise protocol as subregional strain differences within the Achilles tendon are not taken into account. The purpose of this paper is therefore to critically review the published literature that currently exists on Achilles tendon strain in normal Achilles tendons as well as in Achilles tendons with tendinosis. Knowledge on subregional Achilles tendon strain differences may enhance our understanding of the aetiology, pathophysiology and management of Achilles tendinopathy. Methods: The following three databases were examined on November 1 st 2012 using strict search criteria: PubMed, Cochrane Library and CINAHL. The following main keywords were used: "Achilles tendon", "Tendinopathy" and "Strain". These keywords were then expanded to aim for an inclusion of all the relevant literature. Results: Discussion: All included studies in this review concerned global 2D strain measurements. Great variation exists in the measurement technique (ultrasound versus MRI), the location of measurement and the procedure of activation. In the vast majority of the cases, strain is measured in a longitudinal direction over the entire length of the Achilles tendon. Only three studies investigated Achilles tendon strain in transverse direction over the entire thickness of the tendon [Grigg, 2012; Wearing, 2011; Park, 2011]. Values for strain found in literature ranged from 2.1 to 9.2% in the longitudinal direction and from -19.5 to -8.3% in the transverse direction. Moreover, global 2D in vivo Achilles tendon strain in response to Achilles tendinopathy is investigated in only three studies [Grigg, 2012; Arya 2010; Child 2010]. Two-dimensional ultrasound imaging is the preferred imaging technique and maximum voluntary isometric contraction testing is the preferred measurement procedure to assess Achilles tendon strain. Taking into account that strain is a three-dimensional parameter as indicated by subregional strain differences on cadaveric Achilles tendons [Lersch, 2012; Wren, 2003; Lyman, 2004] and considering that Achilles tendinosis can occur at different subregional locations, it is clear that further research regarding non-invasive in vivo intratendinous strain mapping of the healthy and sick Achilles tendon is warranted. References: Arya et al . J Appl Physiol . 2010;108:670–675 Child et al . Am J Sports Med . 201038:1885–1893 Grigg et al . Med Sci Sports Exerc . 2012;44:12–17 Lersch et al . Clin Biomech . 2012;27:955–961 Lyman et al . Am J Sports Med . 2004;32:457–461 Park et al . Foot Ankle Int . 32:407–413 Wearing et al . J Appl Physiol . 2011;110:1384–89 Wren et al . Ann Biomed Eng . 2003;31:710–717